2016
DOI: 10.1073/pnas.1522864113
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-Scale Chemistry of a Calcite Biomineralization Template: Implications for Skeletal Composition and Nucleation

Abstract: Plankton, corals, and other organisms produce calcium carbonate skeletons that are integral to their survival, form a key component of the global carbon cycle, and record an archive of past oceanographic conditions in their geochemistry. A key aspect of the formation of these biominerals is the interaction between organic templating structures and mineral precipitation processes. Laboratory-based studies have shown that these atomic-scale processes can profoundly influence the architecture and composition of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
93
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 52 publications
6
93
3
Order By: Relevance
“…This behaviour has also been reported by Branson et al . (), who conducted experiments on calcium carbonates of foraminifera.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This behaviour has also been reported by Branson et al . (), who conducted experiments on calcium carbonates of foraminifera.…”
Section: Resultsmentioning
confidence: 99%
“…), and calcium carbonate from foraminifera (Branson et al . , Pérez‐Huerta and Laiginhas ). Difficulties in running materials containing organics, namely the evaporation of complex ions (Gordon et al .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Morphological variations of crystal shapes revealed a microbial impact on mineral precipitation (compare Branson et al, 2016). Crystal colors by impurities incorporated into the lattice such as salts or secreted pigments were clearly observed, as calcite can incorporate metal ions in its crystal structure (Kang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Why PREGAM calcite is more susceptible to dissolution than GAM calcite remains unclear, but the selectivity of this dissolution is likely related to the oxidation of organic matter within internal domains and/or the microcrystalline structure and higher Mg composition of PREGAM calcite (Branson et al, 2016;Johnstone et al, 2010Johnstone et al, , 2011Nouet & Bassinot, 2007). Moreover, previous study has shown that diurnal variation in the biological activity of algal symbionts hosted by many mixed layer dwelling planktic foraminifers imparts sequential day-night banding to the PREGAM calcite, with the night bands having higher Mg content (Eggins et al, 2004;Spero et al, 2015;Fehrenbacher et al, 2017).…”
Section: Intersite Differences In Intrashell Dissolution Of Pregam Camentioning
confidence: 99%